Fishers' multidimensional knowledge advances fisheries and aquatic science. (January 2023) - Silvano, Renato A.M.; Baird, Ian G.; Begossi, Alpina; Hallwass, Gustavo; Huntington, Henry P.; Lopes, Priscila F.M.; Parlee, Brenda; Berkes, Fikret
Abstract: Fishers' Indigenous and local knowledge (ILK) has multidimensional contributions to improve fisheries and aquatic ecosystems science, ranging from algae to whales and including management, conservation, ecology, and impact assessment. The challenges are to sustain this knowledge, recognize its value, and to include ILK holders in resource management and decision-making.